Digital platforms, Hindutva, and disinformation: Communicative strategies and the Leicester violence - Dutta MJ (Taylor and Francis Group on behalf of the National Communication Association, 2024)
The digital infrastructure of Hindutva seeds, circulates and amplifies Islamophobic hate, interacting bidirectionally with brick-and-mortar violence. This paper examines the circulation of Hindutva on digital platforms (Twitter, Instagram, YouTube, and Telegram) around the intercommunal violence that emerged in Leicester in September 2022. Based on a digital ethnography of Twitter, interconnected digital platforms, and Hindutva media (Hindutva-related digital video channels such as Citti Media on YouTube, mainstream broadcast media such as NewsX, and text-based digital platforms such as OpIndia), the analysis theorizes the global flow of Hindutva across geographically dispersed contexts, connecting the diaspora with India, creating an uninterrupted communication infrastructure around the frame of the “Hindu in danger,” simultaneously intersecting with white supremacy in producing and amplifying Islamophobic hate.
Keywords: Leicester; Hindutva; violence; digital hate; Islamophobia; Twitter; digital platforms; white supremacy‌